Behaviour and some properties of wood plastic composite made from recycled polypropylene and rubberwood - Abdul Rahman, Azrul Azwan; Joshua, Adeboye Oluwamayowa; Babatope, Adebayo Ademola; Salleh, Mohd Rizal (Hashemite University, 2023)
The current demand for green construction has encouraged the pursuit of alternative products made from new materials such as composite materials built on renewable resources extracted either from nature or, most notably, from industrial waste so that reuse methods can be facilitated. The main focus of this research presented in this article is to study and show the behaviour and some properties of wood plastic composite made from recycled polypropylene and rubberwood when exposed to moisture. Wood polymers have been studied for water absorption properties under cyclical and ageing conditions. In this research, the flexural strength was evaluated before and after water immersion. Water absorption and thickness swelling of wood-recycled polypropylene composites were also studied. A significant relationship was observed between the thickness of the swelling and the increase in the weight gained, the maximum thickness of the swelling and weight increased. To show how flexural strength can be significantly affected by water absorption cycles. Repetition of water absorption cycles has a significant effect on the mechanical properties and effect of the cycle.